Prevalence of self-reported diagnosed cataract and associated risk factors among elderly South Africans - Peltzer, Karl; Crampin, Amelia; Phaswana-Mafuya, Nancy; Ahame, Edmund; Sokhela, Zinhle (International journal of Environmental research and public health, 2017)
This paper estimates the prevalence of self-reported cataract and associated risk factors among individuals aged ≥50 years in South Africa. Data from a nationally-representative cross-sectional Study on Global AGEing and Adult Health (SAGE) (N = 3646) conducted in South Africa from 2007–2008 was analyzed. The primary outcome was self-reported cataract, and exposures included socio-demographics, self-reported co-morbidities, and behavioral factors. Linearized multivariate logistic regression models were used. The weighted prevalence of self-reporteddiagnosedcataractwas4.4%(95%CI:3.4–5.8). Prevalencewasgreateramongindividuals with advancing age (10.2%), higher quality of life (QoL) (5.9%), education (5.2%), and wealth (5.8%) than their counterparts. Prevalence was also higher among individuals with depression (17.5%), diabetes (13.3%), hypertension (9.1%), and stroke (8.4%) compared to those without these conditions, with the exception of obesity (4.2%). In the ﬁnal multivariate model, the odds of self-reported cataract were: 4.14 times higher among people≥70 years than 50 to 59 year olds (95%CI: 2.28–7.50); 2.48 times higher in urban than rural residents (95%CI: 1.25–4.92); 5.16, 2.99, and 1.97 times higher for individuals with depression (95%CI: 1.92–13.86), hypertension (95%CI: 1.60–5.59), and diabetes (95%CI: 1.07–3.61), compared to those without these conditions.
International Journal of Environmental Research and Public Health (2017)14,1523
Keywords: Age-related cataracts; Blindness; Inequalities; Risk factors; SAGE; South Africa; Sub-Saharan Africa; Lower middle income countries; Ageing; blindness